(untitled) (The Pakistan Development Review, 2007)
The economic growth rates have dramatically increased in developing economies, such as in Latin American, Asian, and Eastern European countries, following the financial liberalisation attempt, especially during the 1990s. Foreign direct investment (FDI) has become an increasingly important element for economic development and integration of developing countries and transition economies in this period with the world economy. The main purpose of this study is to develop an empirical framework to estimate the economic determinants of FDI inflows by employing a panel data set of 17 developing countries and transition economies for the period of 1989:01-2006:04. In our model there are seven explanatory economic variables. They are, respectively, the previous period FDI (the pull factor for new FDI), GDP growth (measures market size), Wage (unit labour costs), Trade Rate (measures the openness of countries), the real interest rates (measures macroeconomic policy), inflation rate (as country risk and macroeconomic policy), and domestic investment (Business Climate). Hence, throughout the paper, only the economic determinants (being separated and apart from the other studies in the literature) of FDI inflows to developing countries and transition economies are studied. It is found out that the previous period FDI which is directly related to the host countries’ economic resources is important as an economic determinant. Besides, it is also understood that the main determinants of FDI inflows are the inflation rate, the interest rate, the growth rate, and the trade (openness) rate and FDI inflows give power to the economies of host countries.